A Insights from literature analysis : optimal sunscreen use decreases Melasma incidence in women living in tropical climates - Damayanti, Lina; Pradini, Astri; Salsabila, Mitha (ACTA Medical Health Sciences, 2024)
Melasma is a hyperpigmented patch that is generally found on the face, especiallyon the cheeks, chin, upper lip, and can extend to the neck. The color of hyperpigmentation in melasma varies, generally from light brown to black with an irregular shape. Melasma is often found in countries with tropical climates with skin types III-V. This happens because countries with these climates are exposed to more sunlight. To prevent melasma, it is recommended to use sunscreen to reduce excessive UV exposure to the skin. It is important to use sunscreen optimally in order to reduce the incidence of melasma. The effect of excessive UV exposure to skin, including melasma, can be reduced by applying sunscreen on the regular basis. This literature review used four databases (Google scholar, PUBMED, NCBI and PERDOSKI) and relevant keywords such as